The Morphometric Variation of Human Lips: A Cheiloscopic Study in Forensic Sex Determination - Adrita Mukherjee; Sreedatri Pal; Dibyashree Goswami; Arijit Dey; Diptendu Chatterjee; Biswarup Dey (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Lip print is a common type of evidence found in a forensic context. The determination of the sex from an in-situ lip print is a critical job. Aim and Objectives: The present study aimed to investigate the sexual dimorphism present in lip groove patterns and Cupid’s bow morphology for sex determination. Materials and Methods: The bilateral lip prints were obtained from 100 healthy youths, including 49 males (23.82±8.52) and 51 females (22.25±7.49) from North 24 Pargana District, West Bengal. All the prints were analyzed to quantify total grooves, vertical, cross, and fork-type grooves on both upper and lower lips. Results: Males exhibited a signi𿿿cantly (p<0.05) higher count of vertical grooves on the lower lip, whereas females showed a signi𿿿cantly (p<0.05) higher count on the upper lip. However, the Cross-type grooves were signi𿿿cantly (p<0.05) dominant in both lips of the studied females. Total groove count across both lips was also signi𿿿cantly (p<0.05) higher in females. However, the fork-type grooves in the lower lip showed a signi𿿿cantly higher (p<0.05) count in males. Apart fromthose, Cupid’s bow morphology showed distinct patterns among the males andfemales, V-type structures signi𿿿cantly (p<0.05) predominated in the upper lips of males, while W-type structures were signi𿿿cantly (p<0.05) frequent infemales. However, the lower lip showed signi𿿿cant (p<0.05) sexual dimorphism, withround structures signi𿿿cantly (p<0.05) prevalent in males andÁat structures in emales. Conclusion: Therefore, lip print analysis can be used as a reliable indicator for individual and gender identi𿿿cation in a Forensic context.